Chronic Social Defeat During Adolescence Induces Short- and Long-Term Behavioral and Neuroendocrine Effects in Male Swiss-Webster Mice - Mancha-Gutiérrez, Héctor Miguel; Estrada-Camarena, Erika; Mayagoitia-Novales, Lilian; López-Pacheco, Elena; López-Rubalcava, Carolina (Frontiers in Behavioral Neuroscience, 2021)
Chronic stress exposure during adolescence is a significant risk factor for the development of depression. Chronic social defeat (CSD) in rodents is an animal model of depression with excellent ethological, predictive, discriminative, and face validity. Because the CSD model has not been thoroughly examined as a model of stress-induced depression within the adolescence stage, the present study analyzed the short- and long-term behavioral and neuroendocrine effects of CSD during early adolescence. Therefore, adolescent male Swiss-Webster (SW) mice were exposed to the CSD model from postnatal day (PND) 28 to PND37. Twenty-four hours (mid-adolescence) or 4 weeks (early adulthood) later, mice were tested in two models of depression; the social interaction test (SIT) and forced swimming test (FST); cognitive deficits were evaluated in the Barnes maze (BM). Finally, corticosterone and testosterone content was measured before, during, and after CSD exposure, and serotonin transporter (SERT) autoradiography was studied after CSD in adolescent and adult mice. CSD during early adolescence induced enduring depression-like behaviors as inferred from increased social avoidance and immobility behavior in the SIT and FST, respectively, which correlated in an age-dependent manner with SERT binding in the hippocampus; CSD during early adolescence also induced long-lasting learning and memory impairments in the Barnes maze (BM). Finally, CSD during early adolescence increased serum corticosterone levels in mid-adolescence and early adulthood and delayed the expected increase in serum testosterone levels observed at this age. In conclusion: (1) CSD during early adolescence induced long-lasting depression-like behaviors, (2) sensitivity of SERT density during normal brain development was revealed, (3) CSD during early adolescence induced enduring cognitive deficits, and (4) results highlight the vulnerability of the adolescent brain to social stressors on the adrenal and gonadal axes, which emphasizes the importance of an adequate interaction between both axes during adolescence for normal development of brain and behavior.